A Comparative Study of the Seismic Behavior of Composite (Steel-Concrete) and Reinforced Concrete Structure - Suwal, Rajan; Sherpa, Pasang Chhiring; Bhandari, Nitesh (Nepal Journal of Science and Technology, 2023)
The low weight, high strength, and durability of steel-concrete composite construction have made it quite popular worldwide. However, it is not commonly used in Nepal. For the country, avoiding composite construction when it is economically viable is a great loss. Using composite materials is of particular interest due to their potential to improve performance through rather small changes in manufacturing and construction technologies. Steel concrete composite construction means the concrete slab is connected to the composite beam with the help of shear connectors so that they act as a single unit. In this paper we intend to compare the parameters like storey drift, time period, deflections, etc. between composite and RC structures for 6, 10 and 15 stories regular and irregular buildings situated in earthquake zone V. ETABS software was used for the analysis and linear static method, linear time history method and static pushover method were performed. The results are compared and we found out that composite constructions are more suitable in multi- storied buildings compared to RC structures.